Comparative Study of the Constitutions of Indonesia and China Regarding the Existence of Atheists - Adelia Kartika Nur Huda; Erio Agustia Rachman; Mohammad Ali Sajjad; Cahya Risqi Rusfiyah (CV. Pustaka Parawali, 2024)
This research is based on comparing the Indonesian and Chinese constitutions regarding the existence of atheists and the factors that cause differences in the recognition of the Indonesian and Chinese states against atheism. This research uses normative legal research methods focusing on legal objects with a comparative approach to law and legislation. The existence of atheists in the Indonesian constitution originated from communism with an anti-God attitude contrary to the Indonesian constitution, which is by the first principle of Pancasila and article 29 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. This is very contrary to the Chinese constitution, which regulates freedom of religion and gives the right to embrace or not embrace any religion, meaning that China recognizes the existence of atheists. The Chinese constitution acknowledges the existence of atheists based on the communist ideology adopted.